Designed fabrication of three-dimensional δ-MnO2-cladded CuCo2O4 composites as an outstanding supercapacitor electrode material. (6th November 2018) - Pang, Mingjun; Jiang, Shang; Zhao, Jianguo; Zhang, Sufang; Liu, Rui; Qu, Wenshan; Pan, Qiliang; Xing, Baoyan; Gu, Ling; Wang, Haiqing
Abstract : Three-dimensional δ-MnO2 -cladded CuCo2 O4 composites on Ni foam have been designed via a hydrothermal method followed by one-pot chelation-mediated aqueous processes. Abstract : Three-dimensional δ-MnO2 -cladded CuCo2 O4 composites are designed and grown in situ on Ni foam via a simple hydrothermal reaction and subsequent one-pot chelation-mediated aqueous processes. The electrode architecture can take good advantage of the synergistic effects contributed by both the porous CuCo2 O4 nanoflake core and the δ-MnO2 shell layer. When δ-MnO2 -cladded CuCo2 O4 composites, along with porous Ni foam, are employed as a binder-free electrode for supercapacitors, the hybrid electrode shows higher specific capacitances and a better rate capability than the single CuCo2 O4 nanoflake electrode. A maximum specific capacitance of 1180 F g −1 is achieved at a current density of 1 A g −1 and 81.7% of this value remains at a high current density of 10 A g −1 . Moreover, the δ-MnO2 -cladded CuCo2 O4 electrode also delivers an excellent cycling stability, maintaining 93.2% at 15 A g −1 after 5000 galvanostatic charge–discharge cycles. Moreover, according to electrochemical impedance spectroscopy (EIS) analysis, the δ-MnO2 -cladded CuCo2 O4 electrode possesses a lower equivalent series resistance of 0.78 Ω and a charge transfer resistance of 0.09 Ω. In view of its cost-effective fabrication process and excellent energy storage properties, this unique integrated nanoarchitecture would hold great promise in the field of electrochemical energy storage.